Interface optimization perovskite solar cell and preparation method thereof
By introducing benzyl phosphoric acid as an interface modifier at the interface of perovskite solar cells, the problems of high density of interface defect states and insufficient stability are solved, and the charge transfer efficiency is improved and the device stability is optimized.
Patent Information
- Application Number
- CN202411984823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The interfacial defect state density of existing perovskite solar cells is high, affecting the efficient transmission of charge, and device stability needs to be further optimized.
By introducing different concentrations of benzyl phosphoric acid as an interface modifier between 2PACz and the perovskite layer, an interface optimization layer is formed to improve interface quality.
It effectively reduces the density of interface defect states, promotes charge transfer, improves the efficiency and stability of perovskite solar cells, and reduces manufacturing costs.
Smart Images

Figure CN119836102A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic devices, and in particular to an interface-optimized perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have attracted widespread attention in the field of photovoltaic devices due to their high efficiency and low-cost manufacturing process. The interface quality of perovskite materials has a decisive influence on the performance and stability of devices. Self-assembled monolayer (SAM) technology has been introduced to improve interface quality. Among them, 2PACz (2-(9H-carbazol-9-yl)ethyl phosphate), a commonly used SAM material, has been widely studied due to its good electrical properties and interface control capabilities. However, when using only 2PACz, there is still room for improvement in the interface quality between it and the perovskite layer, especially in reducing the interface defect state density and promoting charge transport.
[0003] While the application of 2PACz has improved the interface quality of perovskite solar cells to some extent, several issues remain with existing technologies. Key issues include a high density of interface defect states, which hinders efficient charge transfer; a need to improve charge transfer efficiency, particularly in terms of photoelectric conversion efficiency; and device stability, as the instability of perovskite materials is one of the main factors limiting their commercial application. Furthermore, the preparation and application of 2PACz in existing technologies can be complex, involving multi-step chemical treatments and precise process control, which increases manufacturing costs and operational complexity. Summary of the Invention
[0004] The present invention aims to address these issues by providing an interface-optimized perovskite solar cell and a method for preparing the same. By adding varying concentrations of benzylphosphonic acid as an interface modifier, the interface quality between 2PACz and the perovskite layer is improved, thereby enhancing the efficiency and stability of the perovskite solar cell. This method aims to reduce the density of interfacial defect states, promote charge transport, and improve the overall performance and stability of the device.
[0005] In order to achieve the above-mentioned purpose, the technical solution of the present invention is as follows: an interface-optimized perovskite solar cell and a preparation method thereof, comprising the following layer structures in contact with each other in sequence: a first charge transport layer, an interface optimization layer, a perovskite layer, a second charge transport layer and an electrode, wherein the interface optimization layer material is benzyl phosphate.
[0006] Furthermore, the thickness of the first charge transport layer does not exceed 10 nm.
[0007] Furthermore, the thickness of the perovskite layer is 300-800 nm, and the thickness of the second charge transport layer is 10-50 nm.
[0008] Furthermore, the surface passivated perovskite solar cell is a regular perovskite solar cell or an inverted perovskite solar cell.
[0009] Furthermore, the interface optimization material is a benzyl phosphate material; benzyl phosphate is a small molecule phosphoric acid that connects the perovskite layer and the hole transport layer, can fill the vacancies between 2PACz and the electrode, is beneficial to reducing the interface defect state density, and promotes charge transfer.
[0010] Another object of the present invention is to provide a method for preparing an interface-optimized perovskite solar cell, comprising the following steps:
[0011] A) adding an interface optimization solution to the first charge transport layer, coating the mixed solution on the surface of the perovskite film, and then heating and curing to form the first charge transport layer and the interface layer; the interface layer solution comprises ethanol and benzyl phosphoric acid, and the concentration of the benzyl phosphoric acid is preferably 0.1-0.5 mg / ml;
[0012] B) coating a perovskite precursor solution on the surface of the first charge transport layer, heating and curing the solution to form a perovskite film;
[0013] C) forming a second charge transport layer on the surface of the interface optimization layer, and evaporating an electrode on the surface of the second charge transport layer to obtain an interface optimized perovskite solar cell.
[0014] Furthermore, the perovskite precursor solution includes an organic salt and an inorganic salt; the organic salt is one or more of FAI, MAI, MACl, FABr and MABr; and the inorganic salt is one or more of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
[0015] Furthermore, the coating method is preferably spin coating, the spin coating speed is preferably 2000-4000 rpm, and the spin coating time is preferably 30-50 s.
[0016] Furthermore, the temperature of the heating annealing is preferably 100-200° C., and the time of the heating annealing is preferably 10-30 minutes.
[0017] Furthermore, the interface optimization solution comprises benzyl phosphoric acid and ethanol, and the concentration of benzyl phosphoric acid is preferably 0.01-1 mg / ml, more preferably 0.01-0.5 mg / ml.
[0018] Compared with the existing technology, the beneficial effects of this solution are as follows: This solution significantly improves the performance of the perovskite solar cell by introducing benzyl phosphoric acid as an interface modifier between the hole transport layer 2PACz and the perovskite layer. First, the introduction of benzyl phosphoric acid effectively fills the vacancies between 2PACz and the electrode, reducing the density of interface defect states. This approach of reducing defect states helps to reduce charge recombination, thereby improving the photoelectric conversion efficiency of the battery. Secondly, benzyl phosphoric acid, as a small molecule phosphoric acid, can promote the transfer of charge at the interface, further improving the performance of the battery. In addition, by optimizing the concentration of benzyl phosphoric acid, this solution can achieve precise control of the interface quality under different preparation conditions, which is crucial to improving the stability and long-term performance of the battery.
[0019] In addition, the present invention simplifies the preparation process and reduces manufacturing costs through common methods such as spin coating, vapor deposition or coating. At the same time, by precisely controlling the concentration of benzyl phosphoric acid and the conditions of heating annealing, this solution can achieve fine regulation of battery performance. These improvements not only improve the photoelectric conversion efficiency of perovskite solar cells, but also enhance the stability of the device, giving this solution obvious advantages in improving energy utilization efficiency and reducing costs. Overall, this solution not only improves the performance of perovskite solar cells through interface optimization strategies, but also provides a feasible technical path for the commercial application of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0021] Figure 1 Schematic diagram of benzyl phosphate passivation of perovskite surface defects;
[0022] Figure 2 Comparison of battery devices without / with benzyl phosphoric acid coating;
[0023] The left picture shows a battery device without benzyl phosphate added, and the right picture shows a battery device with benzyl phosphate added.
[0024] Figure 3 1 is the voltage-current curve of the perovskite battery in the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention will be further described in detail below in conjunction with the embodiments of the present invention and the accompanying drawings. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts should fall within the scope of protection of the present invention.
[0026] The present invention provides an interface-optimized perovskite solar cell, comprising a substrate, an interface-optimized first charge transport layer, a perovskite layer, and a second charge transport layer in contact with each other in sequence;
[0027] The interface optimization material is benzyl phosphoric acid. The schematic diagram of benzyl phosphoric acid passivating the surface defects of perovskite is shown in the attached figure. Figure 1 As shown in the attached Figure 1 It can be seen that the oxygen atoms in benzyl phosphoric acid can replace I / Br vacancies and can also form hydrogen bonds with the hydrogen atoms in FA / MA to be fixed on the perovskite surface, thereby enhancing the passivation effect of benzyl phosphoric acid.
[0028] In the present invention, the substrate is preferably FTO or ITO.
[0029] In the present invention, the first charge transport layer includes one or more of 2PACz, Me2PACz and Me4PACz; the thickness of the first transport layer is preferably 1 to 10 nm, preferably 2 to 5 nm.
[0030] In the present invention, the thickness of the perovskite layer is preferably 300 to 800 nm.
[0031] In the present invention, the interface layer is preferably benzyl phosphoric acid; the thickness of the interface layer is preferably ≤10 nm, more preferably 2-8 nm, and even more preferably 2-5 nm.
[0032] In the present invention, the second charge transport layer comprises one or more of SnO2, TiO2, PCBM and C60; the thickness of the second charge transport layer is preferably 10 to 50 nm, preferably 20 to 40 nm.
[0033] In the present invention, the electrode is preferably Au, Ag or Cu.
[0034] The present invention also provides a method for preparing an interface-optimized perovskite solar cell, comprising the following steps:
[0035] A) adding an interface optimization solution to the first charge transport layer, coating the mixed solution on the surface of the perovskite film, and then heating and curing to form the first charge transport layer and the interface layer; the interface layer solution comprises ethanol and benzyl phosphoric acid, and the concentration of the benzyl phosphoric acid is preferably 0.1-0.5 mg / ml;
[0036] B) coating a perovskite precursor solution on the surface of the first charge transport layer, heating and curing the solution to form a perovskite film;
[0037] C) forming a second charge transport layer on the surface of the interface optimization layer, and evaporating an electrode on the surface of the second charge transport layer to obtain an interface optimized perovskite solar cell.
[0038] The present invention adopts spin coating, vapor deposition or coating to prepare the second electron transport layer on the surface of the substrate, which is a common method in the art and will not be described in detail herein.
[0039] After obtaining the first charge transport layer and the interface optimization layer, the present invention coats the perovskite precursor solution on the surface of the first charge transport layer, then maintains the coated wet film under vacuum conditions for 10 to 30 seconds, and then heats and anneals to solidify the wet film to form a perovskite film.
[0040] In the present invention, the perovskite precursor solution includes an organic salt and an inorganic salt;
[0041] The organic salt is one or more of FAI, MAI, MACl, FABr and MABr; the inorganic salt is one or more of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
[0042] The coating method is preferably spin coating, and the spin coating speed is preferably 2000-4000 rpm, such as 2000 rpm, 3000 rpm, 4000 rpm, preferably a range value with any of the above values as the upper or lower limit; the spin coating time is preferably 30-50 s.
[0043] The inventive concept of passivating the surface of a perovskite solar cell in the present invention is applicable to both regular perovskite solar cells and inverted perovskite solar cells.
[0044] In the present invention, when preparing the first charge transport layer and the interface optimization layer, the heating annealing temperature is preferably 100-200°C, more preferably 100-150°C; the heating annealing time is preferably 10-30 min, more preferably 15-30 min.
[0045] In the present invention, the interface optimization solution comprises benzyl phosphoric acid and ethanol, and the concentration of benzyl phosphoric acid is preferably 0.01-1 mg / ml, more preferably 0.01-0.5 mg / ml, such as 0.01 mg / ml, 0.05 mg / ml, 0.1 mg / ml, 0.5 mg / ml, preferably a range value with any of the above values as the upper or lower limit, most preferably 0.1-0.5 mg / ml.
[0046] When preparing a formal perovskite solar cell, the organic salt and the inorganic salt are dissolved in a solvent respectively to obtain an organic salt solution and an inorganic salt solution. The inorganic salt solution is coated on the surface of the electron transport layer and annealed to form a coating; the organic salt solution is coated on the surface of the coating and annealed to form a perovskite film.
[0047] In the present invention, the inorganic salt coating formed does not require annealing; the annealing temperature after the organic salt solution is applied is preferably 100 to 150°C, more preferably 120 to 150°C; the annealing time for forming the inorganic salt coating is preferably 10 to 15 minutes.
[0048] After obtaining the perovskite layer, the present invention forms an electron transport layer on the surface of the passivation layer by evaporation using a spin coating method, a vapor deposition method or a coating method. This is a common method in the art and will not be described in detail herein. A comparison diagram of the battery device of benzyl phosphate before and after spin coating is shown in the attached figure. Figure 2 shown.
[0049] An electrode is evaporated on the surface of the second charge transport layer to obtain an interface-optimized perovskite solar cell.
[0050] From the attached Figure 2 It can be seen that the addition of benzyl phosphate significantly improves the uniformity and density of the film in the battery device, effectively reducing the occurrence of interfacial defects. This shows that benzyl phosphate, as an interface modifier, not only optimizes the interface bonding between 2PACz and the perovskite layer but also promotes stable film formation, thereby improving charge transfer efficiency. Furthermore, the modified film has higher quality, which helps improve the device's photoelectric conversion performance and long-term stability.
[0051] In the present invention, the electrode is preferably made of gold, silver or copper; the vacuum degree of the evaporation is preferably 0.5 to 2×10 -5 Pa, more preferably 1 to 1.5×10 Pa -5 .
[0052] The present invention provides an interface passivated perovskite solar cell, comprising a cathode, a first charge transport layer and an interface optimization layer; the interface optimization layer is benzyl phosphate; a perovskite layer and a second charge transport layer; at the interface between the first charge transport layer and the perovskite, the benzyl phosphate has the function of filling vacancies, which is beneficial to reducing the interface defect state density and promoting charge transport; the design and introduction of the benzyl phosphate interface optimization layer improves the photoelectric conversion efficiency and device stability of the perovskite solar cell device.
[0053] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments of the present invention can be combined with each other. The present invention will be described in detail below with reference to the embodiments.
[0054] Example 1: A method for preparing an interface-optimized perovskite solar cell, comprising the following steps:
[0055] Prepare the substrate: Use ITO conductive glass (glass thickness 2 mm, ITO film thickness 100 nm) with a size of 1.5×1.5 cm as the substrate of the battery.
[0056] Clean the substrate: Clean the ITO conductive glass with ethanol, isopropyl alcohol (IPA), and acetone for 30 minutes each to remove surface impurities and oil. After cleaning, use a nitrogen gun to blow dry the ITO conductive glass to ensure the surface is dry and free of moisture.
[0057] Prepare the first charge transport layer and interface optimization layer: Weigh 0.5 mg of 2PACz and 0.1 mg of benzyl phosphoric acid into 1 ml of anhydrous ethanol and stir thoroughly to prepare a mixed solution of 2PACz and benzyl phosphoric acid. Apply 40 μL of this solution evenly to the surface of an indium tin oxide (ITO) conductive glass using a spin coater at 2000 rpm for 30 seconds. Anneal the coated ITO glass on a hot plate at 120°C for 30 minutes to form a 2 nm thick, interface-optimized 2PACz film.
[0058] Preparation of the perovskite layer: 600 mg of lead iodide (PbI2) and 17 mg of cesium iodide (CsI) were weighed and dissolved in a mixture of 900 μL of N,N-dimethylformamide (DMF) and 100 μL of dimethyl sulfoxide (DMSO). The mixture was heated and stirred at 70°C to prepare PbI2 precursor solution A. 110 mg of formamidine hydroiodide (FAI) and 23.15 mg of methylamine chloride (MACl) were weighed and dissolved in 1 mL of isopropyl alcohol (IPA) and stirred to prepare organic salt solution B. 20 μL of solution A was evenly coated on the surface of the interface-optimized 2PACz film using a spin coater at 2000 rpm for 50 seconds. Thirty seconds after applying solution A, 40 μL of solution B was evenly coated on the surface of the coating formed by solution A. The coated ITO conductive glass was placed on a hot plate at 100°C and annealed for 30 minutes to form a 400 nm thick perovskite film.
[0059] Preparation of the second charge transport layer and electrode: The formed perovskite film was transferred to a thermal evaporation device and the vacuum degree reached 1×10 -5 Under the condition of Pa, C60 (30 nm) and BCP (7 nm) were evaporated to form the second charge transport layer. Silver (Ag) with a thickness of 100 nm was evaporated on the surface of the second charge transport layer as an electrode.
[0060] Battery packaging: The battery packaging is completed in a nitrogen glove box to ensure the stability and performance of the battery.
[0061] Example 2: A perovskite solar cell was prepared according to the method of Example 1, except that the mass of benzyl phosphoric acid was weighed to be 0.5 mg when preparing the first charge transport layer.
[0062] Example 3: A perovskite solar cell was prepared according to the method of Example 1, except that benzyl phosphoric acid was not weighed when preparing the first charge transport layer, but only 2PACz was weighed.
[0063] Example 4: Performance testing of perovskite solar cells
[0064] The present invention uses PCE to test the current density-voltage (JV) curves of the batteries prepared in the embodiment and the comparative example. The test was completed on the Keysight 2400 system. The test conditions were: the simulated light intensity was 100 mW cm -2 (AM 1.5G) The scanning rate was 0.1Vs-1 (step size was 0.02V, time delay was 200ms), the scanning interval was 1.2V to -0.2V, and the power output of the xenon lamp was calibrated by the KG5 standard Si battery of the NERL (National Renewable Energy Laboratory). The test results are as follows Figure 3And shown in Table 1 below.
[0065] Table 1 Battery performance test results of the examples and comparative examples
[0066]
[0067] from Figure 3 It can be seen that after adding benzyl phosphoric acid, the short-circuit current and fill factor are significantly improved. The benzyl phosphoric acid concentration in Example 2 is 1 mg / ml, compared with 0.5 mg / ml in Example 1, the fill factor is further improved, showing the highest battery efficiency.
[0068] The above specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the embodiments as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by patent law.
Claims
1. An interface optimized perovskite solar cell, characterized by: The invention comprises the following sequentially contacted layer structures: a first charge transport layer, an interface optimization layer, a perovskite layer, a second charge transport layer and an electrode, wherein the material of the interface optimization layer is benzyl phosphoric acid.
2. The interface optimized perovskite solar cell according to claim 1, characterized in that: The thickness of the first charge transport layer is no more than 10 nm.
3. The interface optimized perovskite solar cell according to claim 1, characterized in that: The thickness of the perovskite layer is 300-800 nm, and the thickness of the second charge transport layer is 10-50 nm.
4. The interface optimized perovskite solar cell according to claim 1, characterized in that: The surface passivated perovskite solar cell is a formal perovskite solar cell or an inverted perovskite solar cell.
5. The interface optimized perovskite solar cell according to claim 1, characterized in that: The interface optimization material is a benzyl phosphate material; benzyl phosphate is a small molecule phosphoric acid that connects the perovskite layer and the hole transport layer, can fill the vacancies between 2PACz and the electrode, is beneficial to reducing the interface defect state density, and promotes charge transfer.
6. A method for preparing an interface-optimized perovskite solar cell, characterized in that: The following steps are involved: A) adding an interface optimization solution to the first charge transport layer, coating the mixed solution on the surface of the perovskite film, and then heating and curing to form the first charge transport layer and the interface layer; the interface layer solution includes ethanol and benzyl phosphoric acid, and the concentration of the benzyl phosphoric acid is preferably 0.1-0.5 mg / ml; B) coating a perovskite precursor solution on the surface of the first charge transport layer, heating and curing, and forming a perovskite film; C) forming a second charge transport layer on the surface of the interface optimization layer, and evaporating an electrode on the surface of the second charge transport layer to obtain an interface optimized perovskite solar cell.
7. The preparation method according to claim 6, characterized in that: The perovskite precursor solution includes an organic salt and an inorganic salt; the organic salt is one or more of FAI, MAI, MACl, FABr and MABr; the inorganic salt is one or more of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
8. The preparation method according to claim 6, characterized in that: The coating method is preferably spin coating, the spin coating speed is preferably 2000-4000 rpm, and the spin coating time is preferably 30-50 s.
9. The preparation method according to claim 6, characterized in that: The temperature of the heating annealing is preferably 100 to 200° C., and the time of the heating annealing is preferably 10 to 30 minutes.
10. The preparation method according to claim 6, characterized in that: The interface optimization solution comprises benzyl phosphoric acid and ethanol, and the concentration of benzyl phosphoric acid is preferably 0.01-1 mg / ml, more preferably 0.01-0.5 mg / ml.
Citation Information
Patent Citations
Interface modification material, interface modification ink, interface modification layer and preparation method, product and application thereof
CN117603059A
Hole transport material, application of hole transport material, solar cell and preparation method of solar cell
CN118678856A
Preparation method of self-assembled monomolecular layer in perovskite battery
CN119136623A
Non-halide based passivator for perovskite photovoltaics
WO2023003520A2